Study on Management Leadership Skills and Faculty Research Capability: An Approach Towards Internationalization Status - Jihan A. Labrador (Selected Topics in Humanities and Social Sciences Vol. 4, 2021)
The study endeavored to explore the institutional internationalization efforts through the top management leadership skills and faculty research capability among the State Universities and Colleges (SUCs) in Region XI. It aimed to know the status of the leadership skills of the SUCs heads and the faculty research capability of the institution as assessed by the participants, it also delved to know the extent of the institutional internationalization efforts of the SUCs as assessed by the faculty, and determined how leadership skills and faculty research capability significantly predict the institutional internationalization efforts of the SUCs in Region XI. This research is made use of survey questionnaires administered to 400 professional participants. The method used was descriptive, correlational, and multi-regression analysis as it delved to test the theory of leadership skills among the State Universities and Colleges’ heads, faculty research capability, and their relationship to institutional internationalization efforts. Findings had shown that top management leadership skills and research capability of faculty had influenced the institutional internationalization efforts among SUCs in Region XI.